Preparation method and application of metal crosslinking type helium separation membrane
By introducing TB polymer with highly active metal cross-linking sites into the helium separation membrane, a metal cross-linked helium separation membrane is formed, which solves the problems of low helium separation efficiency and poor selectivity in the existing technology, and achieves high Permeable and highly selective helium separation for industrial applications.
Patent Information
- Application Number
- CN202411638430.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-17
- Publication Date
- 2025-01-24
AI Technical Summary
In the existing natural gas helium separation technology, the separation efficiency of the helium separation membrane material and the separation membrane are low, poor selectivity, and the mechanical properties of the membrane material are insufficient, which seriously restricts the industrial application of this technology.
Develop a metal cross -cross -type cymbal separation film. By introducing TB polymers containing high -active metal cross -linking sites, and using hydroxyl group to promote metal cross -linking reactions at room temperature, to form a three -dimensional network structure with a specific pore diameter distribution. Improve the gas separation performance of the membrane material.
It achieves high permeability and high selectivity of helium gas separation, breaks through the "trade-off" effect between permeability and selectivity of traditional polyimide membranes, and can efficiently separate high-purity helium gas.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to a high-performance metal cross-linked membrane material and a gas separation membrane for separating helium and a preparation method and application thereof, belonging to the field of membrane separation. Background Art
[0002] Helium, with its unique physical and chemical properties such as low boiling point, low density, low solubility, high thermal conductivity and high ionization energy, has shown extensive and irreplaceable application value in the fields of medicine, industry and science. As a strategic rare gas, the efficient extraction and purification of helium is a hot topic in current research. Natural gas is the main source of helium. Although traditional cryogenic separation technology and pressure swing adsorption technology are mature, they have high energy consumption, large investment and difficulty in obtaining high-purity helium. As an emerging technology, membrane separation technology has the characteristics of efficient and continuous process, simple equipment and no use of organic solvents in the process. It is a green and environmentally friendly separation method and shows broad prospects in the field of natural gas helium extraction. Polymer membranes dominate the natural gas helium extraction market with their excellent flexibility, film forming properties and gas separation performance. Traditional polymer membrane materials, such as polyimide, polyether block amide and inherent microporous polymers, dominate the field of gas separation due to their low cost, excellent processing performance and easy large-scale production. Among them, the diversity of polyimide structures provides a broad space for the design and synthesis of high-performance gas separation membranes, making it the preferred material for helium separation applications. However, traditional polyimide membranes have an inherent trade-off effect between permeability and selectivity, which means that increasing permeability often leads to a decrease in selectivity, and vice versa, which is the "trade-off" effect.
[0003] This phenomenon limits the further application and development of polyimide membranes in the field of separation technology. In order to break through this bottleneck, researchers have conducted in-depth research on polyimide materials, focusing on the following aspects: structural modification, polymer blending, cross-linking modification, and filler doping. At the same time, large-scale application of helium separation membranes is also an important direction for future research. Summary of the invention
[0004] In the process of natural gas helium extraction, traditional membrane separation methods often face problems such as low separation efficiency, poor selectivity for helium, and poor mechanical properties of membrane materials, which seriously restrict the industrial application of this technology. Polyimide has attracted much attention due to its excellent heat resistance, mechanical properties and gas separation performance. The microstructure of polyimide membrane has a decisive influence on its gas separation performance. Studies have shown that increasing the free volume of membrane materials and adjusting the pore size distribution are effective ways to improve the separation performance of helium separation membranes. Introducing a rigid and twisted macro-skeleton structure, such as a rigid ring structure or a liquid crystal structure, can significantly reduce the movement of polymer chain segments and increase the gaps between chains, thereby increasing the free volume of membrane materials. Chemical cross-linking introduces cross-linking points between polymer chains to construct a three-dimensional network structure with a specific pore size distribution, thereby achieving a screening effect on gas molecules. By rationally designing and optimizing the microstructure of membrane materials, a natural gas helium extraction membrane with both high permeability and high selectivity can be obtained to meet the urgent demand for high-purity helium in industrial production. The unique rigid V-shaped structure of the base enables it to exhibit excellent performance in the field of gas separation. Therefore, it is particularly important to develop a new type of helium separation membrane with high permeability coefficient and high selectivity. In order to solve the above technical problems, the present invention provides a new type of metal cross-linked helium separation membrane, which forms a twisted structure polymer containing alkynyl, benzene ring, and heterocyclic ring, so that larger gaps are generated between polymer chains, increasing the free volume inside the polymer. At the same time, the formation of a cross-linked network after metal coordination can effectively improve the gas separation performance of the polymer membrane, breaking through the inherent trade-off effect between the permeability and selectivity of the membrane.
[0005] The present invention aims to solve the problems of low separation efficiency and poor selectivity of helium separation membrane materials and separation membranes in the existing natural gas helium separation technology, and provide a metal cross-linked helium separation membrane material with excellent performance and a preparation method thereof. The separation membrane exhibits a medium permeability coefficient and high selectivity in the process of separating helium, and can efficiently separate high-purity helium.
[0006] The invention provides a metal cross-linked helium separation membrane, which is obtained by cross-linking a polymer containing cross-linking active sites with metal ions through coordination cross-linking. The structure of the TB polymer containing highly active metal cross-linking sites is as shown in Formula 1:
[0007]
[0008] Wherein, n is 40 to 60, and the number average molecular weight of the polymer is 30,000 to 50,000 g / mol.
[0009] The first object of the present invention is to provide a method for synthesizing a precursor containing an active site, the method comprising the following steps:
[0010] Under nitrogen protection, N-methylpyrrolidone is added to 3,3'-dimethoxybenzidine and 4,4'-(acetylene-1,2-diyl) diphthalic anhydride, and after they are completely dissolved, toluene is added, mixed evenly, heated to reflux at 130°C for about 3 hours to remove moisture, and after complete dehydration, heated to 140-190°C, reacted for 6-12 hours, discharged into ice water, and separated and purified to obtain a precursor containing active sites;
[0011] In one embodiment, the molar ratio of 3,3'-dimethoxybenzidine to 4,4'-(ethynyl-1,2-diyl)diphthalic anhydride is 2.5-4:1.
[0012] The second object of the present invention is to provide a method for preparing a TB polymer containing highly active metal cross-linking sites, the method comprising the following steps:
[0013] Step 1, placing the precursor containing the active site in an ice water bath, adding formaldehyde dimethyl acetal, and dripping trifluoroacetic acid at a rate of 1 drop / second, reacting for 0.5 to 2 hours, removing the ice water bath, reacting at room temperature for 24 to 72 hours, terminating the reaction with 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0014] Step 2, under the condition of an ice water bath, add TB polymer to a dichloromethane solution, and drop boron tribromide at a rate of 1 drop / second. After the reaction is completed, quench with cold water, and dry to obtain a TB polymer containing highly active metal cross-linking sites;
[0015] In one embodiment, in step 1, the molar ratio of the monomer to formaldehyde dimethyl acetal is 1:1-6, and the ratio of the monomer to trifluoroacetic acid is 1 g:8-15 mL;
[0016] In one embodiment, in step 3, the solid content of the casting solution is: 3 to 5 wt.%;
[0017] In one embodiment, in step 3, the organic solvent comprises at least one of N-methylpyrrolidone, tetrahydrofuran, N-ethylpyrrolidone and N,N-dimethylformamide;
[0018] In one embodiment, in step 3, the pore size of the basement membrane is: 0.1 μm, 0.22 μm, 0.45 μm, 0.8 μm, 1 μm.
[0019] The third object of the present invention is to provide a method for preparing a metal cross-linked helium separation membrane and to use the helium separation membrane for separation of He and N2 and separation of He and CH4.
[0020] Under room temperature conditions, anhydrous ferrous chloride is dissolved in an organic solvent to prepare a uniformly dispersed metal ion solution. A TB polymer containing highly active metal cross-linking sites is dissolved in the above metal ion solution, stirred at room temperature for 6 to 12 hours to obtain a casting solution in which metal ions are uniformly dispersed, and the selective layer is deposited on a polytetrafluoroethylene-based membrane with a pore size of 0.1 to 1 μm by coating, and dried in an oven for 48 to 72 hours to obtain a metal cross-linked helium separation membrane with a selective layer thickness of 10 to 20 μm;
[0021] The gas with a volume fraction of helium of 1 to 60% and a volume fraction of nitrogen of 0 to 30% in natural gas is separated by the metal cross-linked helium separation membrane of the present invention. The gas with a volume fraction of helium of 1 to 60% and a volume fraction of methane of 0 to 30% in natural gas is separated by the metal cross-linked membrane of the present invention;
[0022] In one embodiment, in step 3, the solvent is evaporated and the film is dried in a vacuum oven at 60 to 100° C. for 48 to 72 hours, and the thickness of the obtained polymer film is 5 to 15 μm.
[0023] Beneficial effects:
[0024] 1. All the reaction processes of the present invention are simple, high in yield and low in cost.
[0025] 2. The metal cross-linked helium separation membrane prepared by the present invention has high separation selectivity and high gas permeability. The permeability coefficient of He is ≥15 Barrer, and the selectivity of He / N2 and He / CH4 is ≥150.
[0026] 3. The present invention relates to the field of gas separation membrane technology, and in particular to a new membrane material and a preparation method thereof, which significantly improves the size screening ability and mechanical properties of the helium separation membrane by introducing a TB polymer containing highly active metal cross-linking sites and utilizing hydroxyl groups to promote the metal cross-linking reaction at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of polymer-metal cross-linking reaction.
[0028] Figure 2 It is a gas permeability testing device.
[0029] Figure 3Optical photographs of some metal cross-linked helium separation membranes. a1 is a front photo of the non-cross-linked helium separation membrane in Comparative Example 1, and a2 is a back photo of the cross-linked helium separation membrane in Comparative Example 1; b1 is a front photo of the metal cross-linked helium separation membrane-1 in Example 1, and b2 is a back photo of the metal cross-linked helium separation membrane-1 in Example 1. After comparing the photo data before and after the cross-linking treatment, it can be clearly observed that the color characteristics of the helium separation membrane have undergone significant physical changes, from dark yellow to dark brown. This change serves as intuitive evidence of the effectiveness of the cross-linking process, showing that the internal structure or chemical properties of the membrane material have undergone the expected changes, which may have affected its selective permeability to helium. DETAILED DESCRIPTION
[0030] The following further illustrates the scheme of the present invention by combining the implementation examples, which are not intended to limit the present invention. The raw materials used in this example are all purchased from the market.
[0031] The test method used in the present invention is the constant volume variable pressure method, and the gas permeability of the membrane is measured by a laboratory-made gas permeability performance test device. The test gases are: He, N2, CH4. The specific operation steps are as follows:
[0032] (1) According to the actual size of the sample pool, cut the membrane sample into a disc shape of appropriate size. Then, measure the thickness of each area of the membrane sample and calculate the average value. After completing these preparation steps, carry out the sample loading operation, add the necessary sealing ring, and ensure that the interface is tightly tightened;
[0033] (2) According to the specific requirements of the experiment, set the temperature of the low-temperature constant temperature bath. Then, start the circulation pump to maintain the constant temperature required during the test. At the same time, turn on the other power switches and valves of the device to ensure that the entire system is in normal working condition. Connect the air inlet to the cylinder of the gas to be tested, and open the cylinder valve to allow the gas to flow and purge the device. This process lasts about 10 minutes. After the purge is completed, close valves 1 and 7, start the vacuum pump, and evacuate the device for about 10 minutes. After the vacuum is completed, first close valve 4, and then turn off the vacuum pump. Finally, check the air tightness of the entire device;
[0034] (3) While closing valves 2, 3 and 5, open valve 1 and the main valve of the gas cylinder. This step is to fill the pressure-stabilizing tank with the gas to be tested at one atmosphere of pressure. After the filling is completed, quickly close the main valve of the gas cylinder and valve 1. To detect whether the membrane sample has defects, it is necessary to slowly open valve 2 and closely observe the changes in the readings of the vacuum gauge on the downstream side of the membrane pool. Check whether the sample has defects. After completing the preliminary inspection, close valve 2. Then open the main valve of the gas cylinder and valve 1 again, and continue to fill the pressure-stabilizing tank with the gas to be tested until the pressure reaches 0.2Mpa and then close the valve;
[0035] (4) First, turn on the vacuum pump, and then open valves 4, 3, and 5 in sequence, and perform vacuum treatment on the membrane sample for 2 hours. After the treatment, first close valve 4, then turn off the vacuum pump, and finally close valves 3 and 5. In order to test the error caused by the airtightness of the system, after closing all valves, start recording the change in the vacuum indication number for 30 minutes. This error value needs to be deducted in subsequent data processing;
[0036] (5) After checking the system error, open valve 2 to allow the gas to flow from the pressure regulating tank into the upstream side of the membrane pool, and use the pressure gauge software to record the data of the vacuum degree of the downstream side changing with time. The test time for He is one hour, and the test time for N2 and CH4 is two hours;
[0037] (6) After the test, ensure that the gas in the device is discharged cleanly through the exhaust gas treatment device. Then turn off the power supply of the device and take out the sample after the test.
[0038] 1. The gas permeability parameter calculation method of the present invention:
[0039]
[0040] Where: P is the gas permeability coefficient: Barrer (1Barrer = 1×10 -10 cm 3 (STP) ×cm / (cm 2 ×s×cmHg)); Q is the cumulative amount of gas permeation from the beginning of permeation to time t (cm 3 ); A is the area of the membrane (cm 2 ), l is the membrane thickness (cm), ΔP is the pressure difference between the upstream and downstream sides (Mpa).
[0041] 2. The calculation formula of the gas selectivity involved in the present invention is:
[0042]
[0043] Where: α i / j It indicates that the membrane is an ideal choice for gas components He, CH4 and N2; P irepresents the permeability coefficient (Barrer) of He; Pj represents the permeability coefficient (Barrer) of gas components CH4 and N2.
[0044] Example 1 The preparation process of a metal cross-linked helium separation membrane material is as follows:
[0045] 1. Preparation of precursors containing active sites:
[0046] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0047] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0048] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 24h, terminating the reaction with 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0049] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0050]
[0051] Wherein, n is 48, and the number average molecular weight of the polymer is 35424 g / mol.
[0052] 3. Preparation of metal cross-linked helium separation membrane:
[0053] The concentration of the prepared solution was 1.0×10 -8 mol / L FeCl2 solution, and then dissolving the above polymer in the above solution, the solid content of the casting solution is 3wt.%, and the casting solution is spread on the base film of the organic separation membrane by casting method. Dry in a vacuum oven at 60°C for 24h to obtain a composite membrane with a thickness of 20μm.
[0054] Example 2 The preparation process of a metal cross-linked helium separation membrane material is as follows:
[0055] 1. Preparation of precursors containing active sites:
[0056] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0057] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0058] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 24h, terminating the reaction with 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0059] Step 2: Add 1.0 g of TB polymer to 100 mL of dichloromethane in an ice water bath, and add 0.57 mL of boron tribromide at a rate of 1 drop / second. After the addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites as shown in Formula 1:
[0060]
[0061] Wherein, n is 48, and the number average molecular weight of the polymer is 35424 g / mol.
[0062] 3. Preparation of metal cross-linked helium separation membrane:
[0063] The concentration of the prepared solution was 1.5×10 -8 mol / L FeCl2 solution, and then dissolving the above polymer in the above solution, the solid content of the casting solution is 3wt.%, and the casting solution is spread on the base film of the organic separation membrane by casting method. Dry in a vacuum oven at 60°C for 24h to obtain a composite membrane with a thickness of about 20μm.
[0064] Example 3 The preparation process of a metal cross-linked helium separation membrane material is as follows:
[0065] 1. Preparation of precursors containing active sites:
[0066] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0067] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0068] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 24h, terminating the reaction with 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0069] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0070]
[0071] Wherein, n is 48, and the number average molecular weight of the polymer is 35424 g / mol.
[0072] 3. Preparation of metal cross-linked helium separation membrane:
[0073] The concentration of the prepared solution was 2.0×10 -8 mol / L FeCl2 solution, and then dissolving the above polymer in the above solution, the solid content of the casting solution is 3wt.%, and the casting solution is spread on the base film of the organic separation membrane by casting method. Drying in a vacuum oven at 60°C for 24h, a composite membrane with a thickness of 22μm is obtained.
[0074] Example 4 The preparation process of a metal cross-linked helium separation membrane material is as follows:
[0075] 1. Preparation of precursors containing active sites:
[0076] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0077] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0078] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 36h, and terminating the reaction with a 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0079] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0080]
[0081] Wherein, n is 60, and the number average molecular weight of the polymer is 44880 g / mol.
[0082] 3. Preparation of metal cross-linked helium separation membrane:
[0083] In N-methyl-2-pyrrolidone
[0084] The concentration of the solvent was 1.0×10 -8 mol / L FeCl2 solution, and then dissolving the above polymer in the above solution, the solid content of the casting solution is 3wt.%, and the casting solution is spread on the base film of the organic separation membrane by casting method. Dry in a vacuum oven at 60°C for 24h to obtain a composite membrane with a thickness of about 20μm.
[0085] Example 5 The preparation process of a metal cross-linked helium separation membrane material is as follows:
[0086] 1. Preparation of precursors containing active sites:
[0087] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0088] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0089] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 36h, and terminating the reaction with a 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0090] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0091]
[0092] Wherein, n is 60, and the number average molecular weight of the polymer is 44880 g / mol.
[0093] 3. Preparation of metal cross-linked helium separation membrane:
[0094] The concentration of the prepared solution was 1.5×10 -8 mol / L FeCl2 solution, and then dissolving the above polymer in the above solution, the solid content of the casting solution is 3wt.%, and the casting solution is spread on the base film of the organic separation membrane by casting method. Dry in a vacuum oven at 60°C for 24h to obtain a composite membrane with a thickness of about 20μm.
[0095] Example 6 The preparation process of a metal cross-linked helium separation membrane material is as follows:
[0096] 1. Preparation of precursors containing active sites:
[0097] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0098] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0099] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 36h, and terminating the reaction with a 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0100] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0101]
[0102] Wherein, n is 60, and the number average molecular weight of the polymer is 44880 g / mol.
[0103] 3. Preparation of metal cross-linked helium separation membrane:
[0104] The concentration of the prepared solution was 2.0×10 -8 mol / L FeCl2 solution, and then dissolving the above polymer in the above solution, the solid content of the casting solution is 3wt.%, and the casting solution is spread on the base film of the organic separation membrane by casting method. Drying in a vacuum oven at 60°C for 24h, a composite membrane with a thickness of 23μm is obtained.
[0105] Example 7 The preparation process of a metal cross-linked helium separation membrane material is as follows:
[0106] 1. Preparation of precursors containing active sites:
[0107] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0108] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0109] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 72h, terminating the reaction with 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0110] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0111]
[0112] Among them, n is 73, and the number average molecular weight of the polymer is 54604 g / mol.
[0113] 3. Preparation of metal cross-linked helium separation membrane:
[0114] The concentration of the prepared solution was 1.0×10 -8 mol / L FeCl2 solution, and then dissolving the above polymer in the above solution, the solid content of the casting solution is 3wt.%, and the casting solution is spread on the base film of the organic separation membrane by casting method. Dry in a vacuum oven at 60°C for 24h to obtain a composite membrane with a thickness of about 20μm.
[0115] Example 8 The preparation process of a metal cross-linked helium separation membrane material is as follows:
[0116] 1. Preparation of precursors containing active sites:
[0117] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0118] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0119] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 72h, terminating the reaction with 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0120] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0121]
[0122] Among them, n is 73, and the number average molecular weight of the polymer is 54604 g / mol.
[0123] 3. Preparation of metal cross-linked helium separation membrane:
[0124] The concentration of the prepared solution was 1.5×10 -8 mol / L FeCl2 solution, and then dissolving the above polymer in the above solution, the solid content of the casting solution is 3wt.%, and the casting solution is spread on the base film of the organic separation membrane by casting method. Dry in a vacuum oven at 60°C for 24h to obtain a composite membrane with a thickness of about 20μm.
[0125] Example 9 The preparation process of a metal cross-linked helium separation membrane material is as follows:
[0126] 1. Preparation of precursors containing active sites:
[0127] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0128] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0129] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 72h, terminating the reaction with 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0130] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0131]
[0132] Among them, n is 73, and the number average molecular weight of the polymer is 54604 g / mol.
[0133] 3. Preparation of metal cross-linked helium separation membrane:
[0134] The concentration of the prepared solution was 2.0×10 -8 mol / L FeCl2 solution, and then dissolving the above polymer in the above solution, the solid content of the casting solution is 3wt.%, and the casting solution is spread on the PTFE base film by casting method. Drying in a vacuum oven at 60°C for 24h, a composite film with a thickness of 21μm is obtained.
[0135] Comparative Example 1 Preparation of Uncrosslinked Helium Separation Membrane Material-1
[0136] 1. Preparation of precursors containing active sites:
[0137] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0138] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0139] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 24h, terminating the reaction with 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0140] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0141]
[0142] Wherein, n is 48, and the number average molecular weight of the polymer is 35424 g / mol.
[0143] 3. Preparation of uncrosslinked helium separation membrane:
[0144] Using N-methyl-2-pyrrolidone as solvent, a casting solution with a solid content of 3 wt.% was prepared, and the casting solution was spread on the base membrane of the organic separation membrane by a casting method. The mixture was dried in a vacuum oven at 60° C. for 24 hours to obtain a composite membrane with a thickness of 20 μm.
[0145] Comparative Example 2 Preparation of Uncrosslinked Helium Separation Membrane Material-2
[0146] 1. Preparation of precursors containing active sites:
[0147] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0148] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0149] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 36h, and terminating the reaction with a 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0150] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0151]
[0152] Wherein, n is 60, and the number average molecular weight of the polymer is 44880 g / mol.
[0153] 3. Preparation of uncrosslinked helium separation membrane:
[0154] Using N-methyl-2-pyrrolidone as solvent, a casting solution with a solid content of 3 wt.% was prepared, and the casting solution was spread on the base membrane of the organic separation membrane by a casting method. The mixture was dried in a vacuum oven at 60° C. for 24 hours to obtain a composite membrane with a thickness of 20 μm.
[0155] Comparative Example 3 Preparation of Uncrosslinked Helium Separation Membrane Material-3
[0156] 1. Preparation of precursors containing active sites:
[0157] Add 50 mL of N-methylpyrrolidone to 2.44 g of 3,3'-dimethoxybenzidine and 1.27 g of 4,4'-(ethynyl-1,2-diyl) diphthalic anhydride. After complete dissolution, stir at room temperature for 4 hours, add 20 mL of toluene, mix evenly, and heat to reflux at 130°C for about 3 hours under nitrogen protection to remove moisture. After complete dehydration, heat to 180°C and react for 8 hours. After the reaction is completed, cool to room temperature and turn off nitrogen. Cool the mixture of deionized water and methanol to 0°C, pour the above mixture into the mixture, filter out the precipitate, and wash with deionized water to obtain a precursor containing active sites.
[0158] 2. Preparation of TB polymers containing highly active metal cross-linking sites:
[0159] Step 1, taking 1g of the precursor containing active sites and placing it in an ice water bath, adding 1mL of formaldehyde dimethyl acetal to the system, and dropping 8mL of trifluoroacetic acid at a rate of 1 drop / second, removing the ice water bath after reacting for 1h, reacting at room temperature for 72h, terminating the reaction with 2.5% ammonia solution, washing and drying to obtain a TB polymer;
[0160] Step 2: Add TB polymer to 100 mL of dichloromethane in an ice-water bath, and drop 0.57 mL of boron tribromide at a rate of 1 drop / second. After the drop addition is complete, react at room temperature for 1 hour. After the reaction is completed, quench with cold water and dry to obtain a TB polymer containing highly active metal cross-linking sites:
[0161]
[0162] Among them, n is 73, and the number average molecular weight of the polymer is 54604 g / mol.
[0163] 3. Preparation of uncrosslinked helium separation membrane:
[0164] Using N-methyl-2-pyrrolidone as solvent, a casting solution with a solid content of 3 wt.% was prepared, and the casting solution was spread on the base membrane of the organic separation membrane by a casting method. The mixture was dried in a vacuum oven at 60° C. for 24 hours to obtain a composite membrane with a thickness of 20 μm.
[0165] Result analysis:
[0166] As can be seen from the data in Table 1, the metal cross-linked helium separation membrane of the present invention not only significantly improves the permeability coefficient of helium, but also shows higher He / N2 and He / CH4 selectivity, successfully breaking through the "trade-off" effect of permeability and selectivity of traditional polyimide membrane materials. Further comparison of Examples 1 to 9 shows that the influence of metal ion concentration on the helium permeability coefficient is significant. With the increase of metal ion concentration, the helium permeability coefficient shows a trend of gradual increase, while maintaining a high gas selectivity.
[0167] Table 1: Single component gas permeability performance data
[0168]
Claims
1. A method for preparing a metal cross-linked helium separation membrane material, characterized in that: The separation membrane material is composed of hydroxyl-containing The TB polymer containing highly active metal cross-linking sites is prepared by the following formula: Wherein n is 40 to 60, and the number average molecular weight of the polymer is 30,000 to 50,000 g / mol.
2. A method for preparing a metal cross-linked helium separation membrane material, characterized in that: The method comprises the following steps: Step 1, a diamine monomer undergoes a substitution reaction with an acetylenic anhydride to obtain a precursor containing an active site; Step 2: Using the monomers in step 1 as raw materials, introducing TB groups through polymerization reaction, and then constructing highly active metal cross-linking sites through demethylation reaction to obtain TB polymers containing highly active metal cross-linking sites; Step 3, dissolving anhydrous ferrous chloride in an organic solvent, adding the TB polymer containing highly active metal cross-linking sites in step 2 and stirring to form a casting solution, uniformly coating the casting solution on a polymer base membrane with a certain pore size and pore size distribution, and placing it in an oven to dry, thereby obtaining a metal cross-linked helium separation membrane.
3. The method for preparing a metal cross-linked helium separation membrane material according to claim 2, characterized in that: The concentration of the metal ions is 1.0×10 -8 ~2.0×10 -8 mol / L, the preferred polymer concentration is 1.5×10 -8 mol / L.
4. The method for preparing a metal cross-linked helium separation membrane material according to claim 2, characterized in that: The preparation method of the precursor containing active sites is as follows: Under nitrogen protection, 3,3'-dimethoxybenzidine and 4,4'-(acetylene-1,2-diyl) diphthalic anhydride are dissolved in N-methylpyrrolidone, and a certain amount of toluene is added as a co-solvent. The mixture is refluxed at 130°C for 3 to 4 hours, and then the temperature is raised to 140 to 190°C for reaction for 6 to 12 hours. After the reaction is completed, the nitrogen is turned off after cooling to room temperature, and the mixture of deionized water and methanol is cooled to 0°C. The above mixture is poured into the mixture, the precipitate is filtered out, and washed with deionized water to obtain a precursor containing active sites.
5. The method for preparing a metal cross-linked helium separation membrane material according to claim 2, characterized in that: The preparation method of the TB polymer containing highly active metal cross-linking sites is as follows: Step 1, using trifluoroacetic acid as a solvent, reacting a precursor containing an active site with formaldehyde dimethyl acetal at a molar ratio of 1:1 to 6 at 0 to 5° C. for 0.5 to 2 hours, then reacting at room temperature for 24 to 72 hours, discharging the product into a 2.5% ammonia solution, neutralizing the trifluoroacetic acid with ammonia solution, separating and purifying the product, dissolving the product in N-methylpyrrolidone, filtering the insoluble solid, re-discharging the solution into deionized water, washing and drying to obtain the TB polymer containing the active site; Step 2: Add the TB polymer into dichloromethane to prepare a mass concentration of 20-33.3 mg / mL. Under nitrogen protection, the above solution was cooled to 0°C. Subsequently, boron tribromide was slowly added to the reaction system at a rate of 1 to 3 drops / second, and the molar ratio of the TB polymer containing active sites to boron tribromide was 1:4 to 6. After the addition was completed, the reaction was continued at 0 to 5°C for 2 to 4 hours. After the reaction was completed, the reaction mixture was quickly poured into pre-cooled ice water for quenching, and the TB polymer with highly active metal cross-linking sites was obtained after separation and purification.
6. The method for preparing a metal cross-linked helium separation membrane material according to claim 2, characterized in that: The preparation method of the metal cross-linked helium separation membrane is: Under room temperature conditions, anhydrous ferrous chloride is dissolved in an organic solvent to prepare a uniformly dispersed metal ion solution. A TB polymer containing highly active metal cross-linking sites is dissolved in the above metal ion solution, stirred at room temperature for 6 to 12 hours to obtain a casting solution in which metal ions are uniformly dispersed, and the selective layer is deposited on a base membrane of an organic separation membrane with a pore size of 0.1 to 1 μm by coating, and dried in an oven for 48 to 72 hours to obtain a metal cross-linked helium separation membrane with a selective layer thickness of 10 to 20 μm; The organic reagent includes one or more of N-methylpyrrolidone, N-ethylpyrrolidone and N,N-dimethylformamide; The material of the organic separation bottom membrane includes but is not limited to: fluorine-containing organic polymer bottom membrane such as PVDF, PFA, PTFE or PSF, PES; The pore size of the base film includes but is not limited to: 0.1 μm, 0.22 μm, 0.45 μm, 0.8 μm or 1 μm; The solid content of the casting solution is: 3wt.%, 4wt.% or 5wt.%; The cross-linking metal ion concentration is: 1.0×10 -8 mol / L、1.5×10 -8 mol / L or 2.0×10 -8 mol / L.
7. A method for preparing a metal cross-linked helium separation membrane material according to claim 6, characterized in that the material is dried in a vacuum oven at 60-100°C for 48-72 hours and then dried in a vacuum oven at 100-120°C for 6-12 hours; the thickness of the obtained composite membrane is 20-30 μm.
8. The helium separation membrane material prepared according to claims 1 to 7 can be used for separation of He from N2 and He from CH4.
